Complaint Management Performed at X Public Hospital in Indonesia - Nugraha, Reza; Wulandari, Maulina Pia; Kriyantono, Rachmat (Fakultas Kedokteran Universitas Brawijaya, 2022)
Health consumers or patients become aware of their health literacy by obtaining, processing, understanding, and communicating health-related information when they come to health decisions. However, background knowledge obtained would set patients' expectations and satisfaction, and the expression of patients' expectation gap that creates dissatisfaction or concern with a service provided is called complaint. This present study aimed to obtain a comprehensive understanding about the role and activities of public relations on patient complaint management at X public hospital in Indonesia. This research applied a qualitative method using the purposive sampling technique. The research finding showed that the informants at the hospital lacked communication and public relations knowledge, and no training was given to the staff involved in communication matters. This absence of an academic foundation to guide the work directly affects the professionalism of the public relations manager, especially during managing complaints and making policies. As a result, the public relations department of the hospital did not have a direct channel for the patients to register their complaints, and the only indirect patient complaint facility aimed at the public relations was not managed by the public relations department. In short, this study shows that the public relations manager did not have a management role on the complaint management at the hospital, which consequently brings a snowball effect to the overall management of complaints due to the practices of encroachment, and the hospital must provide more training and professional coaching to bring back the role and functions of public relations.